PENGELOLAAN KEUANGAN BISNIS ONLINE MENGGUNAKAN TELEPON PINTAR - Sahdan Maulana; Ayu Fitrianingrum; Abieza Satya Damara; Enno Astri Quinta; Evie Puspita Sari; Kartiko Hariputra; M. Ilham Mu’arief; Utari Ayuningrum Zuti; Taufik Raharjo (LPPM Universitas Pamulang, 2020)
The object of this community service is SME Dpp.bookstore. The purpose of this community service activity is to raise awareness of the importance of accounting for and equip skills in financial management or accounting with the Android-based